BJVM 2016
DOI: 10.15547/bjvm.866
|View full text |Cite
|
Sign up to set email alerts
|

Study on the prevalence of lipolytic yeasts and moulds in raw cow milk and white brined cheese

Abstract: The extent of microbial contamination with moulds and yeasts of raw cow milk and white brined cheese produced in Bulgarian dairy enterprises was evaluated. The isolation and identification of microorganisms was performed using the classical microbiological methods. The samples of raw milk showed 76.6% contamination with moulds, at average amount of 3.4 log 10 cfu/mL, maximum of 4.8 log 10 cfu/mL. Yeasts were detected in 93.3% of the samples (average 3.5 log 10 cfu/mL). Isolated moulds belonged to the genera As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…According to Chipilev et al (2016), which analyzed white brined cheeses from Bulgarian dairies, produced with heat treated cow milk and vacuum packaged after a ripening period of 45 days, concluded that more than 63% of cheese samples were contaminated with yeast in total counts of 10 2 to 10 6 cfu/g. The present study did not detect the presence of coliform bacteria, coagulase-positive staphylococci, and listeria monocytogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…According to Chipilev et al (2016), which analyzed white brined cheeses from Bulgarian dairies, produced with heat treated cow milk and vacuum packaged after a ripening period of 45 days, concluded that more than 63% of cheese samples were contaminated with yeast in total counts of 10 2 to 10 6 cfu/g. The present study did not detect the presence of coliform bacteria, coagulase-positive staphylococci, and listeria monocytogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Since yeasts and moulds can cause alterations in sensory parameters of dairy products their presence is undesirable [12]. The appearance of yeasts in some acidified dairy products in high numbers may be caused by their ability to grow in low water activities (aw) and low temperatures, and ability to tolerate low pH and high salt concentrations [13].…”
Section: Discussionmentioning
confidence: 99%
“…Species C. parapsilosis (50%) and C. moniliiforme (50%) were identified in the air from the draining room (C3). Among them, the species of C. intermedia, K. lactis, P. kudriavzevii, and R. mucilaginosa are well-known contaminants in white-brined cheese [7,[33][34][35].…”
Section: Diversity Of Yeasts In Cheese Productionmentioning
confidence: 99%